Edukasi deteksi dini HIV/AIDS pada ibu sebagai upaya pencegahan penularan HIV kepada anak - Wardiyah, Aryanti; Setiawati, Setiawati; Rilyani, Rilyani; Riyanto, Eko; Nafisah, Nida; Gusleni, Meri; Maharani, Erliana; Rohmah, Eis Ainun; Marzuna, Marzuna; Sahara, Amalia; Capilo, Pabio Leo (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: HIV/AIDS remains a public health problem, including among mothers and children. Mother-to-child transmission of HIV can occur during pregnancy, childbirth, and breastfeeding, especially if the mother does not know her HIV status early. Purpose: To increase mothers' knowledge and awareness regarding early detection of HIV/AIDS as an effort to prevent HIV transmission in children. Method: This activity was held on November 14, 2025, at 9:00 a.m. WIB at the Cempaka Putih Bumi Waras Integrated Health Post (Posyandu) in Bandar Lampung. Twenty-five mothers living near the Posyandu participated as respondents, and health workers served as facilitators and resource persons. This community service activity used a promotive and preventive approach. The target group was mothers in the community, who play a crucial role in preventing mother-to-child HIV transmission. The material was delivered through an interactive lecture, covering the definition of HIV/AIDS, modes of HIV transmission, the risks of mother-to-child HIV transmission, the importance of early HIV detection, and efforts to prevent HIV transmission in children. To enhance participant understanding, the activity continued with a discussion and question-and-answer session, allowing mothers to ask questions and obtain clarification on the material presented. The activity was evaluated qualitatively through observations of participant participation and enthusiasm during the session, as well as direct feedback from participants after the education. This evaluation aimed to assess the effectiveness of the material delivery and mothers' responses to the educational activities. Results: This activity ran smoothly and received a positive response from participants, who demonstrated enthusiasm throughout the presentation. This was evident in their active listening, asking questions, and participating in the discussion. The community service activity, which provided early detection education for HIV/AIDS to mothers, demonstrated positive results in increasing participants' understanding and awareness of HIV/AIDS and efforts to prevent mother-to-child transmission. Observations indicated an increase in mothers' knowledge regarding HIV/AIDS, including understanding of transmission methods, the importance of HIV testing, and efforts to prevent mother-to-child transmission. Conclusion: The community service activity, which provided promotive and preventive education using an early detection approach for mothers, increased mothers' understanding and awareness of HIV/AIDS, transmission mechanisms, and the importance of early detection as an effort to prevent mother-to-child transmission. This educational activity also encouraged mothers to develop positive attitudes toward prevention efforts, increasing their willingness to utilize health services and understanding the role of early detection in protecting children's health. Suggestion: It is hoped that HIV/AIDS early detection education activities for mothers can continue to be implemented sustainably and reach a wider audience across various levels of society. Education needs to be integrated with maternal and child health programs in health care facilities to ensure wider and consistent access to information about HIV/AIDS and early detection. Furthermore, health workers are expected to play an active role in providing comprehensive education and creating a supportive environment to reduce stigma and increase mothers' trust in health services. Keywords: Early detection; Health education; HIV/AIDS; Mother and child; Prevention of HIV transmission Pendahuluan: HIV/AIDS masih menjadi permasalahan kesehatan masyarakat, termasuk pada kelompok ibu dan anak. Penularan HIV dari ibu ke anak dapat terjadi selama kehamilan, persalinan, dan menyusui, terutama apabila ibu tidak mengetahui status HIV-nya sejak dini. Tujuan: Untuk meningkatkan pengetahuan dan kesadaran ibu mengenai deteksi dini HIV/AIDS sebagai upaya pencegahan penularan HIV pada anak. Metode: Kegiatan ini dilaksanakan pada tanggal 14 November 2025 pukul 09.00 WIB di Posyandu Cempaka Putih Bumi Waras Bandar Lampung. Diikuti oleh 25 orang ibu yang tinggal di lingkungan Posyandu untuk menjadi responden dan melibatkan tenaga kesehatan sebagai fasilitator dan narasumber. Kegiatan pengabdian kepada masyarakat ini menggunakan pendekatan promotif dan preventif. Sasaran kegiatan adalah ibu di lingkungan masyarakat yang memiliki peran penting dalam upaya pencegahan penularan HIV dari ibu ke anak. Materi disampaikan melalui ceramah interaktif meliputi pengertian HIV/AIDS, cara penularan HIV, risiko penularan HIV dari ibu ke anak, pentingnya deteksi dini HIV, serta upaya pencegahan penularan HIV pada anak. Untuk meningkatkan pemahaman peserta, kegiatan dilanjutkan dengan diskusi dan sesi tanya-jawab sehingga ibu dapat menyampaikan pertanyaan serta memperoleh klarifikasi terkait materi yang diberikan. Evaluasi kegiatan dilakukan secara kualitatif melalui pengamatan partisipasi dan antusiasme peserta selama kegiatan berlangsung, serta umpan balik langsung dari peserta setelah edukasi. Evaluasi ini bertujuan untuk menilai ketercapaian penyampaian materi dan respons ibu terhadap kegiatan edukasi yang telah dilaksanakan. Hasil: Kegiatan ini berjalan dengan lancar dan mendapat respons positif dari peserta yang menunjukkan antusiasme selama proses penyampaian materi. Hal ini terlihat dari keaktifan peserta dalam menyimak materi, mengajukan pertanyaan, serta berpartisipasi dalam diskusi yang berlangsung. Kegiatan pengabdian kepada masyarakat berupa edukasi deteksi dini HIV/AIDS pada ibu menunjukkan hasil yang positif dalam meningkatkan pemahaman dan kesadaran peserta mengenai HIV/AIDS serta upaya pencegahan penularan HIV dari ibu ke anak. Terdapat peningkatan pengetahuan ibu mengenai pengertian HIV/AIDS berdasarkan observasi dengan pencapaian pemahaman meliputi cara penularan, pentingnya pemeriksaan HIV, serta upaya pencegahan penularan HIV dari ibu ke anak. Simpulan: Kegiatan pengabdian kepada masyarakat berupa edukasi promotif dan preventif dengan pendekatan deteksi dini HIV/AIDS pada ibu mampu meningkatkan pemahaman dan kesadaran ibu mengenai HIV/AIDS, mekanisme penularan, serta pentingnya deteksi dini sebagai upaya pencegahan penularan HIV dari ibu ke anak. Kegiatan edukasi ini juga mendorong terbentuknya sikap positif ibu terhadap upaya pencegahan dengan memanfaatkan layanan kesehatan menjadi lebih terbuka untuk mencari informasi dan memahami peran deteksi dini dalam melindungi kesehatan anak. Saran: Kegiatan edukasi deteksi dini HIV/AIDS pada ibu diharapkan dapat terus dilaksanakan secara berkelanjutan dan menjangkau lebih banyak sasaran di berbagai lapisan masyarakat. Edukasi perlu diintegrasikan dengan program kesehatan ibu dan anak di fasilitas pelayanan kesehatan agar informasi mengenai HIV/AIDS dan deteksi dini dapat diterima secara lebih luas dan konsisten. Selain itu, tenaga kesehatan diharapkan dapat berperan aktif dalam memberikan edukasi yang komprehensif serta menciptakan suasana yang mendukung untuk mengurangi stigma dan meningkatkan kepercayaan ibu terhadap layanan kesehatan.